Reletationship between ASA Physical Status and Recovery Time After General Anesthesia at RSUD Dr. M. Ashari Pemalang - Agustriliani, Ricke Pramesti; Sukmaningtyas, Wilis; Burhan, Asmat (Java Nursing Journal, 2023)
Background: General anesthesia is a state that changes the physiological condition of the body by removing consciousness, this consists of 3 components namely, hypnotics, analgesics, and muscle relaxation. Patients who have been given anesthetic drugs will recover and regain consciousness. ASA physical status is one of the factors that can determine the length of recovery of consciousness in patients. Methods: The method is a quantitative analytic observational research method with a cross-sectional approach. The sampling technique using consecutive sampling techniques obtained 46 respondents with inclusion and exclusion criteria. Result: The results showed that the most ASA physical status was ASA 2 (47.8%), while the most time to recover consciousness was in the delayed category (56.5%). The correlation test using Kendall's tau showed a significance of p = 0.000 (p < 0.05) with a correlation coefficient of 0.765. Conclusion: There is a strong association between ASA physical status and time to recover consciousness after general anesthesia.